2020
DOI: 10.1021/acs.molpharmaceut.0c00451
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Colorectal Cancer Gene Therapy with IL-15 mRNA Nanoformulation

Abstract: Immunogene therapy is a novel method for the treatment of colorectal cancer. Cytokine IL-15 has exhibited therapeutic anticancer potential due to its immune-stimulation property. However, conventional IL-15-based cancer gene therapy studies have been performed using the plasmid DNA form, which has potential shortcomings including weak delivery efficiency and backbone effect. In this study, an IL-15 immunogene therapy study for colon cancer using in vitro transcript mRNA is described. A protamine/liposome syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…Alternatively to vaccination, a pro-inflammatory tumour microenvironment can be induced by lipid nanoparticle–mRNA formulations delivering cytokines or co-stimulatory molecules 33 , 106 , 161 , 163 , 214 (Table 2 ). For example, mRNA-2416, a lipid nanoparticle encapsulating mRNA encoding human OX40L (a ligand of OX40), is in clinical evaluation for the treatment of patients with solid tumours (NCT03323398) 214 .…”
Section: Preclinical Studies and Clinical Trialsmentioning
confidence: 99%
“…Alternatively to vaccination, a pro-inflammatory tumour microenvironment can be induced by lipid nanoparticle–mRNA formulations delivering cytokines or co-stimulatory molecules 33 , 106 , 161 , 163 , 214 (Table 2 ). For example, mRNA-2416, a lipid nanoparticle encapsulating mRNA encoding human OX40L (a ligand of OX40), is in clinical evaluation for the treatment of patients with solid tumours (NCT03323398) 214 .…”
Section: Preclinical Studies and Clinical Trialsmentioning
confidence: 99%
“… 49 Lei et al synthesized a protamine/cationic liposome system to deliver IL15 mRNA, and this complex was able to treat colon cancer in a lung metastatic tumor model by systemic administration. 50 Pardi et al reported that LNP-supported delivery of modified mRNA resulted in high translation rates for a short time by intravenous administration. 51 …”
Section: Discussionmentioning
confidence: 99%
“…Local or systemic administration of this mRNA induced inhibition of cellular proliferation in several colon cancer models in a safe and efficient way. These results have shown the high therapeutic potential for colorectal cancer immunogenic therapy with this approach [83]. In the same context, Interleukin 2 (IL-2) exerts significant anti-tumor activity.…”
Section: Immunotherapymentioning
confidence: 95%